Positive Politeness Strategy and Social and Culture Value in Convenience Store Woman - Pratama, Tasya; Aryawibawa, I Nyoman; Sudipa, I Nengah (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 2 (2022), 2022)
Language is a representation and an identity for each nation, it is part of the culture. Language is used as a tool to communicate and becomes a path to express other culture and social values. It comes with various forms, one of them is dialogue. Dialogue has an element called positive politeness strategy, a way for people to maintain harmonious relationship with others. Through analyzing dialogues, it also able to uncovers the culture and social value in the environment. Hence this article has the aim to find out what are the positive politeness strategy used by the main character in the novel Convenience Store Woman and what are the culture and social values reflected in it. This article relies on a qualitative method. The source of the data comes from the dialogue of main character (i.e., Keiko Furukura) in the novel Convenience Store Woman and obtained with documentation and observation technique. The data then will be analyzed by applying Content Analysis technique based on Levinson and Brown’s positive politeness strategy (1987). The result shows that there are fifteen positive politeness strategy, Keiko Furukura uses fourteen out of fifteen strategies. She never uses the ‘Joke’ strategy and frequently uses ‘Give gifts to Hearer’ strategy as the answer for the first question. Subsequently, to answer the second question, the culture of zangy? and the society problem about marriage and labor shortage are apparent in the story as shown by the dialogue spoken by Keiko Furukura.